PENGARUH PEMBUANGAN BANIR DALAM PENEBANGAN POHON TERHADAP EFISIENSI PEMUNGUTAN KAYU (Study kasus di suatu perusahaan hutan di Kalimantan Barat) - Sona Suhartana; Maman Mansyur Idris (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
This paper presents the results of the study of the impact of buttress cutting in tree felling on harvestring efficiency. The case study was carried out in PT Kurnia Kapuas Plywood in West Kalimantan in 1994. 771e aim of the study is to know the influence of buttress cutting on wood haversting efficiency.the data were analysed by using the I-test.the result of study shows that average of wood harvesting efficiency by cullting buttress is 68.1 % and without cutting buttress is 66.7 %